The Fruit of Deception: Untangling the Mystery of Adam's Choice in Genesis 3 - Adeoye, Moses Adeleke (Interdisciplinary Journal of Social Sciences, 2024)
The story of Adam and Eve's meeting with the forbidden fruit inside the confines of the Garden of Eden has intrigued theologians and philosophers. The paper thoroughly observes the intricacies of Adam's preference in Genesis 3, losing illumination on the essence of deceit and its effects. By delving into the biblical narrative and scrutinising numerous interpretations, the paper has disclosed the unravelling of the enigma encircling the fruit of deception and its implications for mankind. Through an exhaustive evaluation of the textual content, this paper underscores the significance of Adam's desire and its sizable repercussions. By exploring the serpent's function as a foxy misleader and the susceptibility of human nature, we can gain an extra profound comprehension of Adam's choice's ethical and theological ramifications. Moreover, this scholarly article delves into the theological interpretations surrounding the essence of the fruit. Several teachers contend that the fruit possessed inherent efficiency while others highlight the importance of disobedience and the following estrangement from the divine. Through an exam of these several views, we aim to provide an entire comprehension of the fruit's functions inside the narrative. The descent of humankind and the creation of transgression into the sector are often attributed to Adam's defiance. The article scrutinises the ramifications of this deed, encompassing the forfeiture of purity, the strife inherent in human nature, and the want for salvation. By apprehending Adam's choice and its repercussions, we can grapple with the intricacies of human lifestyles and the ceaseless battle between righteousness and malevolence.